RANCANG ROBOT PEMOTONG RUMPUT OTOMATIS BERBASIS ARDUINO UNO DENGAN SISTEM KENDALI APLIKASI BLYNK - Irawan, Dedi; fitriani, endah (Universitas PGRI Palembang, 2021)
Mowing the grass using manual tools requires more costs and a lot of energy, and also risks fatal accidents for the operator. To overcome this problem, an automatic lawn mower robot that can be controlled via a smart phone is needed, so that its use is more efficient and can reduce costs, lower costs and reduce the risk of work accidents. In the design of the lawn mower robot using the Arduino Uno Microcontroller, NodeMcu as a liaison between the cellphone and Arduino, the Brushless Motor is used for the blades of the lawn mower, the Infrared Sensor is used to detect the density of the grass and to control the speed level of the brushless motor, then the Servo to adjust the height or short. when mowing the grass, Battery as Power Source, and Blynk App as control and control via smartphone. The results of this research robot lawn mower can be implemented to clean the yard and surrounding areas.Â